Interferon-γ and il-10 release assay for patients with ocular toxoplasmosis - Rudzinski, Marcelo Nicolas (2020)
Peripheral blood mononuclear cells (PBMC) from patients with ocular toxoplasmosis were challenged with total antigens from Toxoplasma gondii lysate (TATL) in a cytokine release assay (CRA), run during the inactive period of the disease. Increased interferon gamma (IFN-γ) levels were detected after PBMC stimulation with either ME49 reference strain (P = 0.0015) or local TgCkAr-11-9 isolate (P = 0.0012), as compared with those recorded under basal conditions. TATL from TgCkAr11-9 isolate induced a higher release of IFN-γ than ME49 strain in CRA from all tested patients (P = 0.02). The median value of IFN-γ release on TgCkAr-11-9 stimulation (26.03 pg/mL) allowed the classification of patients into high- or low-/non-IFN-γ releasers. Clinical correlations were established with both groups. The results obtained in this study suggest the need to include local strains when performing CRA with TATL.